OPTIMALISASI KEUANGAN SOSIAL ISLAM SEBAGAI INSTRUMEN EKONOMI PEMBANGUNAN MASYARAKAT - Sirojul Munawwar; Ahmad Mifdlol Muthohar (LPPM STAI Muhammadiyah Probolinggo, 2026)
Islamic social finance is a sharia-based economic instrument that has significant potential to support community development through zakat, infaq, sadaqah, and waqf. This study aims to analyze the role of Islamic social finance in community economic development, identify the challenges in optimizing its management, and formulate development strategies based on Islamic economic principles. The research employs a qualitative approach with a descriptive research type through library research. Data were collected from scientific journals, books, regulations, and other relevant academic sources, and then analyzed using descriptive qualitative techniques. The findings indicate that Islamic social finance plays an important role in poverty alleviation, equitable wealth distribution, and community economic empowerment through the development of productive zakat and productive waqf. The study also reveals that the optimization of Islamic social finance still faces several challenges, including low public literacy, lack of transparency in management, and limited institutional digitalization. Therefore, strengthening institutional governance, implementing digital systems, and enhancing collaboration among stakeholders are essential steps to improve the effectiveness of Islamic social finance in promoting inclusive and sustainable economic development.